2010
DOI: 10.1016/j.fuel.2010.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Sorbent attrition in a carbonation/calcination pilot plant for capturing CO2 from flue gases

Abstract: There is increasing interest in CO 2 looping cycles that involve the repeated calcination and carbonation of the sorbent as a way to capture CO 2 from flue gases during the carbonation step and the generation of a pure stream of CO 2 in the oxyfired calcination step. In particular, attrition of the material in these interconnected fluidized bed reactors is a problem of general concern. Attrition of limestone derived materials has been studied in fluidized-bed systems by numerous authors. In this work, we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 20 publications
4
50
0
Order By: Relevance
“…The carrying capacity here is considered as the uptake of CO2 per mole of the original sorbent; therefore, any attrition of particles that results in losses of material from the bed will reduce the observed carrying capacity from the actual fractional conversion of the particles in the bed. Attrition has been shown to vary across different limestones and treatment methods and to be problematic in FBRs of a similar scale as the one used for this paper (Blamey et al, 2010b, Fennell et al, 2007b as well as on a pilot scale (González et al, 2010). Table 3 shows the mass loss data for all the limestones, after 13 cycles, doped and undoped, with or without steam present.…”
Section: Resultsmentioning
confidence: 99%
“…The carrying capacity here is considered as the uptake of CO2 per mole of the original sorbent; therefore, any attrition of particles that results in losses of material from the bed will reduce the observed carrying capacity from the actual fractional conversion of the particles in the bed. Attrition has been shown to vary across different limestones and treatment methods and to be problematic in FBRs of a similar scale as the one used for this paper (Blamey et al, 2010b, Fennell et al, 2007b as well as on a pilot scale (González et al, 2010). Table 3 shows the mass loss data for all the limestones, after 13 cycles, doped and undoped, with or without steam present.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, using the new insulating mesh materials (with less open area vs. the one used in the subscale development effort) and the new washcoat formulation, the overall volumetric sorbent loadings on the insulating meshes were increased by ~13-20%. The results give potential benefits to the overall adsorber performance (e.g., longer adsorption time, less exposure to thermal cycles, lower overall power consumption, and size benefits) due to the higher sorbent density and thus a higher expected volumetric sorption capacity (i.e., g of CO 2 or H 2 O uptake per cm 3 of adsorber unit). During the sorbent coil assembly, up to eight thermocouples were placed between the "jelly roll" coil layers for temperature readout during the actual adsorption and regeneration process.…”
Section: Scale-up and Design Of Full-scale Adsorber Modulesmentioning
confidence: 99%
“…Furthermore, these sorbent materials can be readily regenerated via either thermal swing adsorption (TSA) or pressure swing adsorption (PSA), and therefore, they are suitable for a continuous control of CO 2 and trace contaminant levels during long duration spacecraft missions. These regenerable adsorber systems do not have to be replaced during mission duration, and can be smaller and lighter than the disposable adsorber beds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, packed beds of sorbent pellets are mostly used in the adsorption systems; however, recent studies have shown that these materials can be easily fluidized and/or eroded, due to both thermal cycling and mechanical vibration, and can generate fine particulates that bypass the downstream mesh filters. [9][10][11] This results in particulates buildup in downstream pumps, blowers, and other components, and has been problematic in some aerospace applications. Furthermore, these packed beds of pellets create a large pressure drop across the adsorption system resulting in high parasitic losses.…”
Section: Introductionmentioning
confidence: 99%